2010
DOI: 10.1136/gut.2010.210567
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of morphological types of intraductal papillary mucinous neoplasms of the pancreas

Abstract: In this multicentre retrospective analysis, the morphological type of IPMN appears to be an independent predictor of patient prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
202
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(222 citation statements)
references
References 22 publications
14
202
3
3
Order By: Relevance
“…Previous studies also demonstrate the greater prevalence of gastric and intestinal IPMN subtypes. 7,8,27 The mixed subtype may have been difficult to assess due to the limited examination of the specimen by all the gastrointestinal pathologists, which is reflected in the poor interobserver agreement for this subtype. Nonetheless, the entirety of each case was seen by a gastrointestinal pathologist at his or her respective institution and the selected slide from each case should be considered representative of the overall lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also demonstrate the greater prevalence of gastric and intestinal IPMN subtypes. 7,8,27 The mixed subtype may have been difficult to assess due to the limited examination of the specimen by all the gastrointestinal pathologists, which is reflected in the poor interobserver agreement for this subtype. Nonetheless, the entirety of each case was seen by a gastrointestinal pathologist at his or her respective institution and the selected slide from each case should be considered representative of the overall lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric and pancreatobiliary subtypes are more often associated with invasive tubular adenocarcinoma versus intestinal subtype, which is frequently associated with invasive colloid carcinoma. [5][6][7][8] Furthermore, studies have reported conflicting evidence on whether the histologic IPMN subtype has prognostic significance. [8][9][10][11][12] The Verona consensus meeting in 2013 recently led to the publication of guidelines for pathologic reporting of IPMN with the recommendation that pathologists provide a histologic subtype.…”
mentioning
confidence: 99%
“…2,5 Concerning pancreatic intraductal papillary mucinous neoplasm, the existence of four different subtypes (intestinal, gastric, pancreato-biliary and oncocytic) is well established, 6 and prognostic differences among subtypes have been described. [7][8][9][10] In addition, several studies performed on human and transgenic mice revealed a number of genetic changes in key molecular pathways during intraductal papillary mucinous neoplasm development. [11][12][13][14][15][16] In contrast to the more common pancreatic intraductal papillary mucinous neoplasms, intraductal papillary neoplasms of the bile duct have not been well characterized so far, either from the clinical or from the molecular point of view.…”
mentioning
confidence: 99%
“…According to histological features (architecture and cytology), four types of IPMNs, such as gastric, intestinal, pancreatobiliary, and oncocystic, have been described. Gastric-type epithelium is frequent in side branches type with better prognosis (malignant potential 28%); intestinal-type and pancreatobiliary-type epithelia are more frequent in main duct type with bad prognosis (malignant potential 60%) [30]. Several patients can be symptomatic with non-specific symptoms.…”
Section: Intraductal Papillary Mucinous Neoplasms (Ipmns)mentioning
confidence: 99%